2019
DOI: 10.1136/bcr-2018-227030
|View full text |Cite
|
Sign up to set email alerts
|

Robust response to nivolumab in patient with renal cell carcinoma inferior vena cava tumour thrombus

Abstract: A 47-year-old previously healthy man presented with acute moderate flank pain. Evaluation revealed left renal cell carcinoma, with inferior vena cava tumour thrombus invasion. Patient had no significant history or risk factors to pre-dispose him to genitourinary cancers. Surgery was deemed to not be appropriate due to distant metastases, but patient received targeted molecular therapy and immunotherapy with striking regression of the thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“… 1 Additionally, a case report of a 47-year-old male with mRCC and IVC tumour thrombus who at baseline had no evidence of PE or deep venous thrombosis and had an IVC filter insitu was started on nivolumab. One year after initiation of treatment but 4 months following investigations demonstrating absence of TEs, he developed a diffuse distribution of thromboses in superior and inferior mesenteric veins, splenic vein and portal vein 5 that parallels a significant hypercoagulable state post IO therapy which occurs in our case.…”
Section: Discussionsupporting
confidence: 59%
“… 1 Additionally, a case report of a 47-year-old male with mRCC and IVC tumour thrombus who at baseline had no evidence of PE or deep venous thrombosis and had an IVC filter insitu was started on nivolumab. One year after initiation of treatment but 4 months following investigations demonstrating absence of TEs, he developed a diffuse distribution of thromboses in superior and inferior mesenteric veins, splenic vein and portal vein 5 that parallels a significant hypercoagulable state post IO therapy which occurs in our case.…”
Section: Discussionsupporting
confidence: 59%
“…Considering that recent studies have observed dramatic reduction of tumor thrombus in ccRCC patients after ICB therapy [ 23 26 ], we speculated that tumor-infiltrating immune cells may play important roles in the process. Therefore, we first performed unsupervised clustering of T and NK cells and obtained 12 clusters across ARTs, PTs and TTs, including four subtypes of CD4 + T cells (CD4-C1 to CD4-C4), five subclusters of CD8 + T cells (CD8-C1 to CD8-C5), two NK subclusters (NK1 and NK2) and one NKT cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are evidences showed that certain CD8 + T cells in the progenitor exhausted state could enhance the efficacy of immune checkpoint blockade (ICB) therapy in melanoma and kidney cancer [ 37 , 38 ]. Meanwhile, considering a striking regression of TTs with ICB therapy in some ccRCC patients [ 23 26 ], we asked whether there was certain subset of CD8 + T cells we recovered may resemble the progenitor exhausted phenotype. Then, we scored the CD8 + T cell subclusters for progenitor and terminally exhausted gene signatures according to the published studies [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstaging of the VTT through neoadjuvant treatment with ICIs can play an important role in minimizing surgical complications. The positive impact of the use of ICIs as neoadjuvant therapies in aRCC and mRCC cases with VTT has been reported [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%